(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to measure the effectiveness of systemic thinking skills to master the skill performance in drawing perspective for second-grade intermediate students in art education. To study this, the researcher determined to build teaching plans for the subject of perspective drawing, according to (systematic thinking skills). The following two null hypotheses were formulated: -There are no statistically significant differences at the significance level (0.05) between the grades of the students of the two groups (experimental and control) in the skill proficiency test. (previously). -There are no statistically significant differences at the significance level (0.05) between the grades of the students of the two groups (experimental and control) in the skill proficiency test (post). The results of this research showed the effectiveness of teaching plans according to (systematic thinking skills) to master the skill performance of the experimental group students. Which had a positive effect on the skill proficiency in the subject of perspective drawing, to reach the desired results.